PERSEPSI WISATAWAN JERMAN TERHADAP KUALITAS PELAYANAN PRAMUWISATA BERBAHASA JERMAN DI DENPASAR - Made Artajaya; Kadek Novie Krisna Yanti (JURNAL KEPARIWISATAAN, 2020)
The number of foreign tourists visiting Indonesia has increased every year. One of the services to meet the needs of tourists while traveling is a travel agency that serves travel servicesthe frequent occurrence of complaints to the service guide, it is necessary conducted research on the perception of German tourists towards the service quality of German speaking guide. This research will analyze the perception of German tourists as a service user of German speaking guide.The assessment will refer to the five dimensions of quality services, namely tangibles, reliability, responsiveness, assurance and empathy. Through this research will be known the aspects of good, which is necessary maintained, and bad aspects, which need to be fixed. For obtain data, applied techniques of documentation study, interview, observation, and distributing questionnaires to 100 German tourists as research samples. Data analysis method used is quantitative descriptive based on scale Likert. Based on the results of this study revealed that the respondents on average has an assessment and good perception with an average rating of 3,71.